Gender differences in the perception of quality of life of patients with colorectal cancer - Trinquinato, Isadora; Marques da Silva, Rodrigo; Ticona Benavente, Sonia Betzabeth; Antonietti, Camila Cristine; Siqueira Costa Calache, Ana Lúcia (Investigación y Educación en Enfermería, 2017)
Objective. to identify the gender differences in assessing quality of life of patients undergoing chemotherapy treatment for colorectal cancer. Methods. this is a cross- sectional investigation conducted with 144 patients (72 men and 72 women) undergoing chemotherapy treatment in a southeastern Brazilian hospital. Data were gathered trough a sociodemographic and clinical information form and the Health-related Quality of Life instrument from the European Organization for Research and Treatment of Cancer. Results. cognitive function leads to lower general quality of life, with higher effect in men when compared to women. Body image (p=0.023), bdominal pain (p=0.020) and dry mouth p=0.001) produced lower quality of life in women. On other hand, men showed lower quality of life related to the following symptoms: fecal incontinency (p<0.001), sexual impotency (p=0.027) and sexual arousal (p<0.001). Conclusion. the illness symptoms and hemotherapy treatment effects tha negatively impact on quality of life differ between men and women. Thus, healthcare needs to be focused on these specific factors that affect the quality of life according to the patient’s gender. How to cite this article: Trinquinato I, Silva RM, Benavente SBT, Antonietti CC, Calache ANSC. Gender differences in the perception of quality of life of patients with colorectal cancer. Invest. Educ. Enferm. 2017; 35(3): 320-329.